Effect of Storage of Fresh Cassava in Sawdust on Gari Processing - Babarinsa, Olumuyiwa Adekanmi; Oluwalana , Isaac Babatunde (Journal of Postharvest Technology, 2018)
Fresh cassava was harvested and stored for twelve weeks in sawdust with careful handling and processing method. Gari was produced from the stored cassava every two weeks throughout the period of storage. Effect of storage on gari yield, ease of peeling and peel pulp ratio was also evaluated. The result of the analysis shows that gari yield decrease as the storage time increase but peel pulp ratio relatively increase with increase storage time and there was no difference in the ease of peeling. The cassava stored well in the sawdust with relative humidity range of 70-80% and temperature range of 28-33 °C.